Community Perception as a Catalyst for Economic Growth and Digital Transformation in BRICS Integration - Anam, Khoirul; Prayogo, Imam (Journal Economic Business Innovation, 2024)
Purpose: To investigate the sensitive nature of the interaction of social perception, economic development, and digitization in brics integration situation. As the global power dynamic continues to shift with the rise of international entities such as BRICS, analyzing the impact of public sentiment and economic transformation on technological innovation has become vital for policymakers and business executives alike.Method: The study uses descriptive statistics with advanced SEM analysis performed on responses collected across diverse respondents partial to the four derivatives. A Likert-scale questionnaire that targeted viewpoints on public perception, economic growth, and digital transformation was developed, and the hypothesized associations among these core elements were tested using multiple regression and SEM techniques.Findings: Economic growth is heavily impacted by public perception and economic growth in turn plays a crucial role in shaping digital transformation. Moreover, public perception was identified as a mediator between BRICS integration and economic growth and digital transformation was found to play a moderating role between societal perceptions and economic outcomes.Novelty: This study reveals new insights into how the perceptions of society not only impact the economy but also how the digital transformation is strengthening these effects. The new approach, applying mediation and moderation effects within the theme of BRICS integration which has not been previously utilized in other studies.Implications: This study provides important insights into how societal perception can be shaped for the better and how it contributes to economic growth and technological advancement, offering important implications for policymakers as well as business leaders. Moreover, the findings highlight the key importance of digital transformation as a moderating factor in the economic development process, especially highlighted in emerging markets.